Adopting High Fat Diets for Fat Loss and Improving Brain Health. - Vaishnavi Nashte; Rutuja Shinde (International Journal of Nutrition, 2020)
With an increased intake of processed carbohydrates and refined sugars, the obesity rate has shot up in the past decade giving rise to mental and physical health problems. These individuals are also the most vulnerable to a number of other diseases including the current pandemic of Covid-19. This paper aims to address the knowledge gap that is required to promote a healthy lifestyle for mental and physical wellbeing. The paper also analyses a number of different studies conducted and helps in understanding obesity as a strong risk factor to various disorders. Despite constant recommendations from healthcare organisations to address the importance of weight regulation, the process to do so often remains uncertain to the general population. The paper analyses the effects of the ketogenic diet for fat loss as well as treating mental illnesses and aims to address the influence of high carbohydrate diets on mental illnesses.
Keywords: Obesity